The Relationship Between Industry Concentration and the Level of Operating Segment Disclosure: The Moderating Effect of Audit Quality - Salem Elhoshy, Mohamed Mahmoud; Elsayed Elhennawy, Elsayed Mahmoud; Juma Zaytoun, Mohamed Khamis (International Journal of Accounting and Financial Reporting, 2024)
This study aimed to examine the relationship between the degree of industry concentration which the company belongs and the level of operating segment disclosure. The study also aimed to test the impact of audit quality on the previous relationship, using a sample of 40 non-financial companies listed on the Egyptian stock exchange for five-year period 2016-2020. Using regression analysis, the results of the study showed a low level of operating segment disclosure in Egyptian companies in general. The results of the study also showed that there is a significant negative relationship between the degree of industry concentration and the level of operating segment disclosure. While the results showed an insignificant negative effect of audit quality on the relationship between the degree of industry concentration and the level of disclosure of the operating segments. The previous results were supported by robustness tests conducted by including additional control variables that include the board of directors’ characteristics, as well as using an alternative measure to measure the degree of industry concentration.